PERSAINGAN BISNIS DALAM KULTUR SOSIAL ETNIK CHINA - Salioso, Herdi (Aksara Public, 2017)
This risert to inpired from a feature film A Chinese Tall Story with Starring Charlene Choi and Nicolas Tse actors and Produsers Albert Lee of Emperor Motions Pictures, wich the background story of 500 years ago, where the legend of western Chinese is already so advanced in the world trade. This risert can be called by local merchants and is currently controlled by the Chinese bisnis enterpreniuer with various types merchandise, especially at the top level. Using a socio-economic-history, this study is being pinned on direct observation and in-dept interviews were conducted against several key figures group Chinese is located in Jalan Setia Budi the authors refers to as Business Area Fifty Setia Budi District of Pekanbaru City; red) on the side of history. At the begining of the years 70 – 80 late, very difficult to find their Chinese enterpreneur in the region, but after nearly 30 years passed in fact be reversed, which is very difficult to find enterpreneur and now over 90 percent of a successful enterpreneurs here is Chinese enterpreneurs.